Sistema de costeo por actividad en la producción de camarones en cautiverios, en la camaronera Jama de la compañía agrícola y piscícola Cevallos Muñoz - Espinel Arroyo, Vanessa Pierina (2019)
The purpose of this research work was to design a costing system by activity for the improvement of the productive management of the Jama shrimp farm, belonging to the Cevallos Muñoz farm and fish company. To achieve this objective, a methodological process was developed covering three central parts: in the first instance, the activities used for the implementation of a cost system based on activities (ABC) were identified: subsequently, the processes included in the production, by means of an interview applied to the owner of the organization and an observation sheet, managing to characterize each of the activities involved in the process of pre-breeding as well as pisciana, from this, the map and record of processes was elaborated; and as a final phase, the costs were assigned to each activity that is part of the shrimp production process, determining the indirect fixed costs, direct labor, and direct bonus material, which allowed obtaining a result of 16622.76 pounds. of shrimp sold, for the price of 1.65, obtaining a return of $ 11,797.42. This indicates that the inclusion of a system of costing system by activity contributes to improve the productive management of Jama shrimp.